Quasi-Static Cyclic Response of Unidirectional Thin-Ply Hybrid Composites - Putu Suwarta; Gergely Czel; Mohamad Fotouhi; Marco L. Longana; Sutikno Sutikno; Michael R. Wisnom (JMES The International Journal of Mechanical Engineering and Sciences, 2021)
Quasi-static cyclic loading of unidirectional (UD) thin-ply hybrid composites was conducted to assess the extent of stiffness loss with increasing applied strain. For this study, three types of hybrid configuration were examined: SG1/MR401/SG1, SG1/TR301/SG1, SG1/TR302/SG1, where SG is a high strength glass fibre and MR40 is an intermediate modulus carbon fibre while TR30 is a standard modulus carbon fibre. The strain at first carbon ply failure and the knee point strain (εk) for the SG1/TR301/SG1 hybrid is higher than for the SG1/TR302/SG1 hybrid. This is due to the ‘hybrid effect’ which provides a delay in damage initiation due to a constraint on broken carbon cluster development. For SG1/MR401/SG1 and SG1/TR302/SG1 configurations, the stiffness reduction over the course of loading was governed by fragmentation of the carbon plies and delamination between the carbon and glass plies. A smaller stiffness reduction for the SG1/TR301/SG1 configuration compared to the other hybrid configurations was observed with the fragmentation of the carbon ply as the main damage mechanism responsible for the reduction. With each loading cycle, there was a small amount of hysteresis and residual strain. The response of the UD thin-ply hybrid laminates are considered pseudo-ductile because the damage in the form of ply fragmentation and stable delamination, leads to gradual loss of stiffness. The stable delamination of this hybrid material is due to the low energy release rate of the thin carbon ply.